Malunion of the Acetabulum Treated by Intra-articular Buttress - D. Saragaglia; J. Gaillot (Case Reports in Orthopedics)
Acetabulum malunions are extremely difficult to treat, and for many years, surgical indications have been dominated by total hip replacement. We treated a protruding acetabular malunion, 20 years ago, using an intra-articular buttress, by means of an allograft corresponding to a femoral head fragment which had been cryopreserved. The radiological and clinical result with this extended follow-up is quite remarkable, which has motivated us to present this original technique.